1972
DOI: 10.1017/s0022172400022300
|View full text |Cite
|
Sign up to set email alerts
|

Water-borne typhoid fever caused by an unusual Vi-phage type in Edinburgh

Abstract: SUMMARYInvestigation of a small series of cases of typhoid fever infected in a river between 1963 and 1970 revealed that all were caused by a single source, a carrier of a rare phage type of Salmonella typhi. The contamination of the river resulted from an incorrect sewage connexion with a surface water drain outfall into the river.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…The Moore swab was first deployed by Brendan Moore in 1948 to trace Salmonella Paratyphi B from sewage in North Devon, England to determine the sources of contamination responsible for sporadic outbreaks of paratyphoid fever. Since the first application to detect typhoidal Salmonella in sewage, the Moore swab method has been utilized in several studies throughout the world to detect Salmonella Typhi in irrigation water, surface water, municipal sewers, and storm drains (Bowmer et al, 1959;Callaghan and Brodie, 1968;Conn et al, 1972;Sears et al, 1984). Given its effectiveness, simplicity, and affordability, we adapted this method for use in typhoid environmental surveillance of wastewater in Kolkata, India.…”
Section: Discussionmentioning
confidence: 99%
“…The Moore swab was first deployed by Brendan Moore in 1948 to trace Salmonella Paratyphi B from sewage in North Devon, England to determine the sources of contamination responsible for sporadic outbreaks of paratyphoid fever. Since the first application to detect typhoidal Salmonella in sewage, the Moore swab method has been utilized in several studies throughout the world to detect Salmonella Typhi in irrigation water, surface water, municipal sewers, and storm drains (Bowmer et al, 1959;Callaghan and Brodie, 1968;Conn et al, 1972;Sears et al, 1984). Given its effectiveness, simplicity, and affordability, we adapted this method for use in typhoid environmental surveillance of wastewater in Kolkata, India.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first application to detect typhoidal Salmonella in sewage, the Moore swab method has been utilized in several studies throughout the world to detect Salmonella Typhi in irrigation water, surface water, municipal sewers, and storm drains. 11,[30][31][32] Given its effectiveness, simplicity, and affordability, we adapted this method for use in typhoid environmental surveillance of wastewater in Kolkata, India. We found that the Moore swab method has several advantages over UF in terms of greater sensitivity, simplicity, shorter processing time, less labor, and lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Phage typing has been particularly important in support of epidemiological investigations of Salm. typhi (Conn et al 1972 Although phage typing is essential for the primary subdivision of serovars, the method can prove insufficiently discriminatory in serovars in which a small number of phage types predominate. For example, from 1981 to 1986, 86% of strains of Salm.…”
Section: A P P L I C a T I O N O F P H E N O T Y P I C T Y P I N G M mentioning
confidence: 99%